PENGARUH KETERAMPILAN BERKOMUNIKASI SAINS MENGGUNAKAN PENDEKATAN MULTIPLE REPRESENTATIONS TERHADAP LITERASI SAINS SISWA - Putri Deryati; Abdurrahman -; Nengah Maharta (Jurnal Pembelajaran Fisika, 2013)
The results of a comparative study was conducted by PISA 2009 showed that the mean score of science literacy test in Indonesian students is still relatively low. Some of the factors that cause are learning in school activities tend to be centered on teachers, so it makes the students get difficult to develop their science communication skills, besides students' ability to interpret the data from a representation to another representation is still low. One of efforts that can assist to improve the students’science literacy especially in newton law material is to develop students' science communication skills. The objective of this research is to determine the effect of science communication skills using Multiple Representation learning approach to science literacy of junior high school students. Sample class is selected by cluster random sampling. The research design that is used one-shot case study. The results showed that there is a positive and significant effect between science communication skills through Multiple Representations approach to science literacy of junior high school. Both variables have a strong correlation, that is 0.61 with a contribution is 37%.Keywords: science communication skills, Multiple Representations learning approach, and students’ science literacy.